Sifat Sensoris Dan Kimia Selai Kelapa Muda (Cocos nucifera L) Dan Buah Naga Merah (Hylocereus polyrhizus) - Thio, J.; Djarkasi, G. S.S.; Lalujan, L. (Fakultas Pertanian, Universitas Sam Ratulangi, 2018)
Jam is a semi-solid food ingredient that can be smeared and made from at least 45 parts by weight of a fruit pulp and 55 parts by weight of sugar. Coconut is one of the best known and widely distributed palms in the tropics. One of the derivative products that can be processed from coconut is jam. Red dragon fruit contains Î²-sianin which has a red-purple color and functions as a natural pigments. This research aims to obtain the preferred formulation of coconut jam and red dragon fruit by evaluating several chemical properties. This research used a completely randomized design with treatment of the ratio between coconut and red dragon fruit (100%; 90%: 10%; 80%: 20%; 70%: 30%; 60%; 40%; 50%: 50%) and replicated three times. Parameters analyzed were water content, total acid, total sugar and sensory evaluation for color, smell, taste, and smear. The results showed that the formulation of coconut jam and red dragon fruit preferred by the panelists was treatment of 70% coconut + 30% red dragon fruit with a value of color 5.84 (like), smell 5.32 (rather like), taste 5.12 (rather like), smearing power 5.56 (easy to smear), moisture content 34.71%, total acid 0.37%, total sugar 43.59%.Keywords : coconut, red dragon fruit, jam